A Comparison of Academic Achievement in the Subject of Factors Affecting in Career on Communication Circumstances and Personality Development between Learning by Experiential Technique with Skill Exercises Activities and Normal Learning - Ardwichai, Ratanada; THAO VAN, NGUYEN; Makemuengthong, Chomphunut (Chophayom Journal, 2023)
The objectives of research were 1) to develop learning activities on factors that influence on career communication circumstances and personality development through experiential technique with skill exercises for second-year students in Thai Language for Communication with the 75/75 criteria 2) to compare the academic achievement between the students who studied through experiential technique with skill exercises and normal learning and 3) to study the students’ satisfaction with organizing learning activities on things that influence career communication circumstances and personality development through experiential technique with skill exercises and normal learning. The sample in this research was 45 second-year students retrieved from using a cluster random sampling from the population who were 67 secondyear students in the Thai language for Communication, and divided into 2 groups 1) the treatment group of students studied with experiential technique with skill exercises and 2) the control group of 20 students studied with normal learning. The instruments included 1) 12 lesson plans 2) the academic achievement test of 30-item multiple choices, and 3) the satisfaction questionnaire in a five-scale questionnaire of 10 items. The statistics used for data analysis were percentage, mean, standard deviation, and T-test was used to analyse Independent Samples. The results of the research showed that: 1) Organizing learning activities using experiential technique together with skill exercises had E1/E2 of 73.93/76.93, indicating that it was effective in accordance with the 75/75 criteria and normal learning had E1/E2 of 72.40/71.67, showed that it wasn’t effective in accordance with the 75/75 criteria. 2) Students’ academic achievement with experiential technique with skill exercises was higher than students who received normal learning with a statistical significance level of .05. 3) Students were satisfied with organizing learning activities with experiential technique with skill exercises overall at a very high level ( = 4.72, S.D. = 0.35), whereas normal learning at a very high level ( = 4.58, S.D. = 0.46). Keywords: Academic Achievement, Communication Circumstances, Personality Development, Experiential Technique